Development of ibuprofen microspheres using acetylated plantain starches as polymer for sustained release (2018)
Ibuprofen has a short half-life (1–3 h) and istypically administered 3–4 times daily with subsequent adverse side effects. A good approach to reduce these effects is the preparation of sustained-release formulations of ibuprofen. Acetylated starches form water-insoluble, acid-resistant films that can substantially retard drug release. Ibuprofen microspheres were prepared using acetylated plantain starch as sustained-release polymer. Starch obtained from unripe plantain (Musa Paradisiaca normalis) were acetylated using acetic anhydride with pyridine (degrees of substitution, DS 1.5 ± 0.05 and 2.20 ± 0.10). The starches were characterized using morphology, crystallinity, swelling, density and flow properties. Ibuprofen microspheres were prepared by quasi-emulsion solvent diffusion method, using acetylated plantain starches DS 1.5 and 2.20 in comparison to Eudragit S100. Full 32 factorial experimental design was performed with polymer type (X1), polymer: drug ratio (X2) as independent factors; microsphere size, entrapment, and quantity of drug released in 12 h (Q12) were dependent variables. The data from in vitro drug release were fitted to various kinetic models. Acetylation resulted in larger starch aggregates with disruption in crystalline order. Ibuprofen microspheres were spherical with size 5.50 ± 4.00–129.90 ± 12.97μm. Drug entrapment was 43.92 ± 4.00–79.91 ± 6.15%. Values of Q12 ranged from 20.10 ± 0.55 to 54.00 ± 5.71%. Interaction between variables X1 and X2 had positive effects on size and entrapment. Drug release fitted zero order, first order and Baker-Lonsdale kinetic models. Acetylated starch of plantain with DS 2.20 was suitable as a polymer at polymer:drug ratio 4:1 for the formulation of ibuprofen microspheres with prolonged drug release.